Articulação compensatória associada à fissura de palato ou disfunção velofaríngea: revisão de literatura - Marino, Viviane Cristina de Castro [UNESP]; Dutka, Jeniffer de Cássia Rillo; Pegoraro-Krook, Maria Inês; Lima-Gregio, Aveliny Mantovan (CEFAC Saúde e Educação, 2012)
TEMA: articulação compensatória na fissura palatina. OBJETIVO: contribuir para o aprofundamento de informações sobre os tipos de articulação compensatória descritos na literatura e, ainda, discutir as implicações e contribuições da avaliação clínica e instrumental na identificação destas produções. CONCLUSÃO: as articulações compensatórias merecem a atenção de clínicos e pesquisadores que atuam no Brasil, já que estas alterações são encontradas com grande freqüência em crianças e adultos com fissura palatina ou disfunção velofaríngea, o que compromete a qualidade de vida destes sujeitos. Os fonoaudiólogos devem aprofundar seus conhecimentos sobre os tipos de articulação compensatória e os procedimentos de avaliação, bem como devem estabelecer programas preventivos que favoreçam a aquisição fonológica sem o desenvolvimento dessas compensações.

BACKGROUND: compensatory articulation in cleft lip and palate. PURPOSE: to contribute with information regarding the types of compensatory articulation described in the literature and discuss the implications and contributions of clinical and instrumental evaluation of these speech productions. CONCLUSION: compensatory articulation deserves attention from Brazilian physicians and researchers, since that these productions occur in children and adults with cleft palate and velopharyngeal dysfunction, compromising their speech intelligibility and consequently quality of their lives. Speech-language pathologists need to improve knowledge regarding different types of compensatory articulation and also on the procedures for evaluating these productions, in order to settle preventive programs that favor phonological acquisition in children with cleft palate without developing compensatory articulation.
Compensatory articulation associated to cleft palate or velopharyngeal dysfunction: literature review
Keywords: Fissura Palatina; Fala; Distúrbios da Fala; Transtornos da Articulação; Cleft Palate; Speech; Speech Disorders; Articulation Disorders